Penerapan Model Two Stay Two Stray (TSTS) Berbantuan Mind Mapping Pada Pembelajaran IPAS - Putri Ayu Meinanda; Ani Fiani; Citra Raflesia (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
This study aims to determine the completeness of the science learning outcomes of fifth grade students of SD Negeri 03 Karya Sakti in the 2025/2026 academic year after implementing the Two Stay Two Stray learning model. The research method used is the Pre-Experimental Design method. With a population of all fifth-grade students totaling 20 students determined by saturated sampling. The data collection technique uses a multiple-choice test with 20 questions. The collected data was analyzed using the Z test. Based on the results of the research and discussion, an average score of 77.81 was obtained with learning completion of 85%. Based on the results of the Z test analysis at a significance level of α = 0.05, Z count 4.21 > Z table 1.64 was obtained, which shows that Ha is accepted and Ho is rejected. So, it can be concluded that the results of the science learning of Class V students of SD Negeri 03 Karya Sakti using the Two Stay Two Stray learning model assisted by Mind Mapping were significantly complete.